EFEK PIJAT TERHADAP PERUBAHAN TEKANAN SISTOLIK ANKLE PASIEN DIABETES MELITUS TIPE 2 - Tetra Saktika Adinugraha (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Peripheral blood vessels diseases in lower extremities is one of the complications of type 2 diabetes mellitus. This condition requires attention from the nurse by acknowleding the ankle systolic pressure and increasing the vasodilation of the peripheral blood vessels. Those can be achieved by applying a massage using effleurage, petrissage or kneading lightly movement techniques. Complementary therapy such as massage therapy has not been applied and comprehended for its effect on ankle systolic pressure. Objective: To identify the differences of the ankle systolic pressure changes by massage therapy in patients with type 2 diabetes mellitus. Methods: This study was a quasi-experiment with case-control design pretest and posttest. Population was patients with type 2 diabetes mellitus treated at Kota Semarang Hospital and Tugurejo Semarang Hospital. A sample of 33 respondents were recruited using purposive sampling technique. A massage therapy using effleurage, petrissage or kneading techniques on the feet, legs, and back was applied for 30 minutes, 2 times a week for 3 weeks. The Wilcoxon test and Mann-Whitney were employed to analyse the data. Result:There was a significant difference on the ankle systolic pressure before and after treatment in intervention group with the p-value of .0001 (p<0.05). There was not a significant difference on the ankle systolic pressure before and after treatment in control group with the p-value of .199 (p<0.05). There was not significant differences from giving a massage to the ankle systolic blood pressure in the intervention group than the control group with the p-value of .086 (p>0.05). Conclusions: There are significant differences on the ankle systolic blood pressure before and after a massage in the intervention group. However, when compared with the control group there was not a significant difference. This study suggests that nurses may use massage therapy using effleurage and petrissage or kneading techniques as a complementary therapy as their independent intervention. Keywords: Diabetes mellitus, Ankle Systolic Pressure, Massage